A threat to our integrity – Meanings of providing nursing care for older patients with cognitive impairment in acute care settings. Issue 1 (28th April 2015) - Nilsson, Anita; Rasmussen, Birgit H.; Edvardsson, David
Abstract : Background: Older people with cognitive impairment represent a large group of patients in acute care settings. Research show that these acute care environments can be unsafe and even unfriendly for frail older patients. Research and clinical experience show that being a nurse in acute/specialised medical facilities means to work in a high‐speed, technologically complex and demanding environment. When caring for older patients with cognitive impairment, nurses' workload and responsibilities have been shown to increase. This is largely dependent on how easily it is to connect with and help patients understand what to do, and what is best for them. Aim: This study aimed to illuminate meanings of caring for older patients with cognitive impairment in acute care settings as experienced by nursing staff. Method: A purposeful sample of thirteen nurses experienced in caring for older people with cognitive impairment in acute care settings participated in the study. Narrative interviews were conducted during autumn 2012 and interpreted using a phenomenological hermeneutic method. Findings: Caring for older, acutely ill cognitively impaired patients was found to be very complex. The meanings of caring for these older patients seemed to change depending on the nurses' perceptions of the patients and the gap between what they could do (real) and wanted to do (ideal) in providing care for them. The greater this gap was felt to be and the more care was perceived as meaningless, the more serious was the threat to nurses' personal‐professional integrity which could be at risk, compromised or harmed. Conclusion: The comprehensive understanding indicates that being a nurse and having to care for older patients in acute care settings means providing nursing care in an environment that does not support possibilities to protect and develop nurses' personal–professional integrity.